Systemic CD4 cytotoxic T cells improve protection against PRRSV-1 transplacental infection - Li, Yanli; Díaz, Ivan; Martín-Valls, Gerard; Beyersdorf, Niklas; Mateu, Enric (Frontiers in Immunology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the major swine pathogens causing reproductive failure in sows. Although modified-live virus (MLV) vaccines are available, only partial protection against heterologous strains is produced, thus vaccinated sows can be infected and cause transplacental infection. The immune effector mechanisms involved are largely unknown. The present study investigated the role of cytotoxic lymphocytes, including cytotoxic T cells (CTL), NKT, and NK cells, in preventing PRRSV1 transplacental infection in vaccinated primiparous sows (two doses vaccinated). Sows from a PRRSV1 unstable farm were bled just before the last month of gestation (critical period for transplacental infection), then followed to determine whether sows delivered PRRSV1-infected (n=8) or healthy (n=10) piglets. After that, we compared functions of CTL, NKT, and NK cells in two groups of sows. No difference was found through cell surface staining. But upon in vitro re-stimulation with the field circulating virus, sows that delivered PRRSV1-free piglets displayed a higher frequency of virus-specific CD107a+ IFN-γ-producing T cells, which accumulated in the CD4+ compartment including CD4 single-positive (CD4 SP) and CD4/CD8α double-positive (CD4/CD8α DP) subsets. The same group of sows also harbored a higher proportion of CD107a+ TNF-α-producing T cells that predominantly accumulated in CD4/CD8α double-negative (CD4/CD8α DN) subset. Consistently, CD4 SP and CD4/CD8α DN T cells from sows delivering PRRSV1-free piglets had higher virus-specific proliferative responses. These data strongly suggest that CTL responses correlate with protection against PRRSV1 transplacental infection, being executed by CD4 T cells or CD4/CD8α DN T cells.